Inhibitory effects of the crude extract from Phomopsis sp. on several pathogenic fungi - Rasidan, Rasyiffa' Hayati (2019)
Endophytic fungi inhabiting plant hosts may contain fungitoxic properties and can be useful for biological control agents. An isolate of Phomopsis sp. from the mangrove tree has been determined if it has possessed antifungal properties. In this study, Phomopsis sp. was cultured in Potato Dextrose Broth (PDB) for 14 day. After which the mycelia were removed, the filtered culture was subjected to liquid-liquid extraction using ethyl acetate (EtOAc) as the solvent. Then, it was purified through a chromatography column using various solvents. Two eluents, hexane (PH) and the mixture of hexane + methanol (PMH), when tested against the pathogenic fungus (Ceratocystis fimbriata) gave 25% inhibitory effect. These findings indicate extraction of secondary metabolite from Phomopsis sp. have the antifungal ability as it can be used as biological control agent.